SYSTEMATIC LITERATURE REVIEW (SLR): THE INFLUENSCE OF DUAL-ROLE CONFLICT ON WOMEN EMPLOYEES PERFOMANCE - Arlianto, Setijo (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study employs a Systematic Literature Review (SLR) approach to analyze the impact of dual-role conflict on female employees' performance. Dual-role conflict arises when women are required to balance professional and domestic responsibilities, which often leads to psychological stress, emotional exhaustion, and time management challenges. Method: A Systematic Literature Review (SLR) is conducted to assess various studies related to dual-role conflict and its influence on women's productivity and performance quality. Results: The findings indicate that time-based, strain-based, and behavior-based conflicts significantly affect women’s productivity and performance quality. Key factors contributing to dual-role conflict include high workloads, inflexible work schedules, cultural expectations, traditional family roles, and a lack of support from partners or workplaces. The study highlights strategies to mitigate these conflicts, such as flexible working arrangements, managerial support, employee training on time management, and shared domestic responsibilities within families. Novelty: This research concludes that unresolved dual-role conflict can result in long-term negative effects, such as burnout, decreased job commitment, or career changes. Recommendations are provided for organizations, policymakers, and individuals to implement gender-inclusive policies and develop holistic solutions to address dual-role conflict effectively.